PENGARUH PENGETAHUAN DAN SANKSI PAJAK TERHADAP KEPATUHAN: KUALITAS PELAYANAN SEBAGAI PEMEDIASI (SAMSAT DOMPU) - Nur Haerunisyah; Ega Saiful Subhan; Hermansyah Hermansyah (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Low taxpayer compliance remains a challenge for optimizing regional revenue. This research aims to investigate the direct effect of tax awareness and tax penalties on compliance among motor vehicle taxpayers, and to assess the intermediary role of service quality at the Samsat Office in Dompu Regency. A quantitative methodology was adopted using primary data gathered through Likert-scale surveys from 100 motor vehicle taxpayers chosen by purposive sampling. The data were then analyzed using PLS-SEM with the assistance of SmartPLS 4.0. The results indicate that tax awareness, tax penalties, and service quality have a significant and positive impact on taxpayer compliance. Furthermore, service quality partially mediates the relationship between tax awareness and tax penalties on compliance. In conclusion, both cognitive and coercive elements require supportive services to effectively enhance compliance. Therefore, it is suggested that the government of Dompu Regency focus simultaneously on improving tax literacy, enforcing penalties consistently, and transitioning to digital services to maximize Motor Vehicle Tax revenues.